HLA and interleukin 1 gene polymorphisms in primary biliary cirrhosis: associations with disease progression and disease susceptibility. Issue 3 (1st March 2001) - Donaldson, P; Agarwal, K; Craggs, A; Craig, W; James, O; Jones, D
Abstract : BACKGROUND AND AIMS: Twin and family studies suggest that there is a genetic component to primary biliary cirrhosis (PBC) but the genetic associations which have been described are weak with marked variations between centres. PBC is heterogeneous and genetic associations with disease progression may be obscured when the PBC population is analysed only as a whole and not subdivided. METHODS: We have investigated two candidate gene loci in 164 well characterised patients, 88 (54%) of whom had advanced disease. RESULTS: There was an increased frequency of the HLA DRB1*0801-DQA1*0401-DQB1*0402 haplotype in patients who had progressed to late stage disease (23% v 2% of controls; p=0000044; odds ratio (OR) 15.5, 95% confidence interval (CI) 3.52–68.4) but not in those with early stage disease (4% v 2%). Patients had a higher frequency of the IL-1B*1, 1 genotype and lower frequencies of the IL-1B*1, 2 and *2, 2 genotypes (p=0.00078; OR 2.37, 95% CI 1.38–4.06), and higher frequency of the IL-1RN*1, 1 genotype and lower frequency of the IL-1RN*1, 2 genotype (p=0.0011; OR 2.28, 95% CI 1.34–3.89). The difference in the IL-1B*1, 1 genotype distribution was most marked in patients with early stage disease (77% v 43% of controls; p=0.000003; OR 4.8, 95% CI 2.31–10) but the IL-1RN genotype distribution was similar in patients with early and late stage disease. CONCLUSIONS: These data indicate a complex relationship between immunoregulatory genes and PBC. While the IL-1 genes are markers of both disease susceptibility and progression, HLA genes appear to be principally associated with disease progression.